Case report on paratesticular sarcoma and a focused review of the literature - Shah Abhijit; Kumar Siddhant; Choudhari Arghya; Chawla Arun; Surag K.R. (Archive of Oncology)
Insidious, usually painless, and rare inguinoscrotal masses arising from paratesticular elements (spermatic cord, epididymis, tunica or the stroma) are known as paratesticular tumors. The overall incidence is less than 5%, and the total number of giant (>10cm) paratesticular liposarcomas is less than 300 cases recorded since 2020. We report a similar clinical dilemma of a giant scrotal mass managed via a wide local resection and close surveillance in a 61 year old male. However, owing to its rarity, there is no fixed treatment protocol; hence, a supplementary review of similar cases is discussed here.